Menimbang Harapan dan Kenyataan dalam Penggunaan Proton Pump Inhibitor sebagai Tata Laksana Gastritis: Suatu Kajian Literatur dan Perspektif Klinik - Danda Ananda; Dewa Ngakan Nyoman Karyana; Baiq Afra Nurfadilah; Farhan Aqil Putra Hermawan; Muthiah Rahmahdani; Ni Luh Putu Eka Widya Ananta Putri; Nurhidayati (LPPM STIKES Mataram, 2026)
Abstract Introduction: Gastritis is common gastrointestinal disorder characterized by inflammation of the gastric mucosa caused by various factors, including excessive gastric acid secretion. Proton Pump Inhibitors (PPIs) are widely used in the management of gastritis due to their effective mechanism in suppressing gastric acid production. Objective: To comprehensively review the role of PPIs in the management of gastritis, including their history, definition, mechanism of action, classification, effectiveness as monotherapy or in combination, as well as potential adverse effects and their prevention. Method: This study employed a literature review method with a descriptive qualitative approach. Articles were retrieved from PubMed, ScienceDirect, and Google Scholar using the keywords